Hexaaquanickel(II) tetraaquabis(μ-pyridine-2,6-dicarboxylato)bis(pyridine-2,6-dicarboxylato)trinickelate(II) octahydrate - Safaei-Ghomi, Javad (International Union of Crystallography, 2010)
The title compound, [Ni(H(2)O)(6)][Ni(3)(C(7)H(3)NO(4))(4)(H(2)O)(4)]·8H(2)O, was obtained by the reaction of nickel(II) nitrate hexahydrate with pyridine-2,6-dicarboxylic acid (pydcH(2)) and 1,10-phenanothroline (phen) in an aqueous solution. The latter ligand is not involved in formation of the title complex. There are three different Ni(II) atoms in the asymmetric unit, two of which are located on inversion centers, and thus the [Ni(H(2)O)(6)](2+) cation and the trinuclear {[Ni(pydc)(2)](2)-μ-Ni(H(2)O)(4)}(2−) anion are centrosymmetric. All Ni(II) atoms exhibit an octahedral coordination geometry. Various interactions, including numerous O—H⋯O and C—H⋯O hydrogen bonds and C—O⋯π stacking of the pyridine and carboxylate groups [3.570 (1), 3.758 (1) and 3.609 (1) Å], are observed in the crystal structure.